POLA PENGASUHAN ISLAMI SEBAGAI AWAL PENDIDIKAN KECERDASAN EMOSIONAL - Rahayu, Iin Tri (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2005)
There are three models of child mothering: authoritative, permissive, and democratic. The good mothering pattern is pattern of mothering which can grow all child intelligence potencies: spiritual, emotional, rational, social, natural, physical, etc. emotional intelligence is potency of intelligence that involves the ability to control feeling and emotion, in guiding mind and action of our self and others.The Islamic mothering pattern is pattern of mothering prioritizing fitrah Islami of child, beside other potencies: spiritual, emotional, rational, social, natural, physical, etc. That is placing forward training and forming of moral, it is so central in forming and developing emotional intelligence of child.Keywords: emotional intelligence and Islamic mothering